2023
DOI: 10.3390/life13010175
|View full text |Cite
|
Sign up to set email alerts
|

Mediation Effect of Pain on the Relationship between Kinesiophobia and Postural Control: Comparison and Correlations in Individuals with Fibromyalgia Syndrome and Asymptomatic Individuals—A Cross-Sectional Study

Abstract: Background: Individuals with fibromyalgia syndrome (FM) usually present with a fear of movement (kinesiophobia), which causes their symptoms to be maintained and exacerbated. Kinesiophobia can significantly impact postural control; ascertaining their association is crucial in evaluating and managing individuals with FM. This study aims to (1) compare postural control between individuals with FM and asymptomatic individuals, (2) estimate the relationship between kinesiophobia and postural control in individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Pain has the ability to influence numerous aspects of the nervous system, including the sensitivity of muscle spindles and the way the central nervous system modulates proprioceptive afferent signals [ 59 ]. Asiri et al [ 37 ] conducted a study investigating the mediation effect of pain on the relationship between kinesiophobia and postural control in fibromyalgia syndrome, and the results demonstrated that pain significantly mediated their relationship to produce altered motor control, hence impacting balancing ability. Similarly in our study, pain may have impacted the relationship between kinesiophobia and LJPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain has the ability to influence numerous aspects of the nervous system, including the sensitivity of muscle spindles and the way the central nervous system modulates proprioceptive afferent signals [ 59 ]. Asiri et al [ 37 ] conducted a study investigating the mediation effect of pain on the relationship between kinesiophobia and postural control in fibromyalgia syndrome, and the results demonstrated that pain significantly mediated their relationship to produce altered motor control, hence impacting balancing ability. Similarly in our study, pain may have impacted the relationship between kinesiophobia and LJPS.…”
Section: Discussionmentioning
confidence: 99%
“…Increased pain is associated with increased proprioceptive errors and decreased balance and functional mobility [ 32 ]. Previous studies have shown that pain is a significant factor that can increase fear of movement and impair motor control [ 33 , 34 , 35 , 36 , 37 ]. However, it is unknown how pain influences kinesiophobia and its relationship with LJPS in CLBP individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Each item is rated on a 4-point Likert scale, with responses ranging from "strongly disagree" to "strongly agree". The total score on the TSK provides an indication of an individual's level of kinesiophobia, with higher scores reflecting a greater fear of movement [26][27][28][29][30].…”
Section: Kinesiophobiamentioning
confidence: 99%
“…These modifications can significantly alter the afferent proprioceptive input, hence affecting the joint position sensation and stability limits [21]. Chronic persistent pain might exacerbate FMS patients' fear of movement, hence diminishing their proprioceptive and balance abilities [21]. These findings demonstrate that kinesiophobia may serve as a mediator between cervical JPS and limitations of stability in patients with FMS.…”
Section: Introductionmentioning
confidence: 98%
“…These altered activation patterns can result in somato-motor-system-related muscular weakening and atrophy [20]. These modifications can significantly alter the afferent proprioceptive input, hence affecting the joint position sensation and stability limits [21]. Chronic persistent pain might exacerbate FMS patients' fear of movement, hence diminishing their proprioceptive and balance abilities [21].…”
Section: Introductionmentioning
confidence: 99%